The scarring effects of deep contractions - David Aikman; Mathias Drehmann; Mikael Juselius; Xiaochuan Xing (Bank of Finland, 2022)
We find that deep contractions have highly persistent scarring effects, depressing the level of GDP at least a decade hence. Drawing on a panel of 24 advanced and emerging economies from 1970 to the present, we show that these effects are nonlinear and asymmetric: there is no such persistence following less severe contractions or large expansions. While scarring after financial crises is well known, it also occurred after the deep contractions of the 1970s and 1980s that followed energy price shocks and restrictive monetary policy to combat high inflation. These results are very robust and have important implications for policy making and macro modelling.
urn:nbn:fi:bof-202210031404
Keywords: E32; E37; G01; 330; Hysteresis; nonlinearity; financial crises; monetary policy; oil shocks